Pengaruh Kualitas Layanan terhadap Kepuasan Nasabah ( Studi pada Nasabah Tabungan Simpeda Bank Kalsel Cabang Ahmad Yani ) - Azis Nurhakim; Yudi Ferianta; Setio Utomo (JURNAL BISNIS DAN PEMBANGUNAN, 2014)
The purpose of the research is to investigate and analyze the quality of service which is measured based on the people and physical aspectswhich have a partial and simultaneous influence on the customer satisfaction;moreover, from these two aspects, it is investigated which aspect is more dominant on the customer satisfaction for Simpeda Savings at Bank Kalsel Branch Ahmad Yani.The research approach used is quantitative one with explanatory research type, and the research location is Bank Kalsel Branch Ahmad Yani. The population of the research is customers of Simpeda Savings at Bank Kalsel Branch Ahmad Yani with a total sample of 302 respondents. Analysis of the data used Multiple Linear Regression analysis techniques; to test the simultaneousinfluence F Test is used and to test partial influence T Test is used at significance level of 0.05.The results of the research proved that the quality of service which is measured based on the people and physical aspects have a partial effect where the result of data processing using the t test found that the t count for the people aspect is 5,048 and t count for the physical aspect is 3,792 while the t table known 1.6499 or if it compared to the t count > t table which can be concluded that there is a partial influence of both aspects on customer satisfaction at Bank Kalsel Branch Ahmad Yani. People and physical aspects also influence simultaneously on customer satisfaction which is proved by the results of the F test–from the data processing– it is obtained the value of F count is 273.173 and the F table is at 3,03, so F count > F table or it can be concluded that the people aspect and physical aspect have a simultaneous influence on customer satisfaction. The people aspect is the dominant aspect on the customer satisfaction because it has the value coefficient of beta β0,467 which is higher than coefficient of beta β forthe physical aspect which is 0,351.This research discovered that the people aspect is the dominant aspect that gives an influence on the customer satisfaction; it is different from results of previous research by FitriHernadi (2013) conducted at Bank Kalsel Branch Tanjungin which the physical aspect is a more dominant aspect in influencing the customer satisfaction.Keywords: service quality, customer satisfaction